Crack Propagation and Microstructural Evolution of Ni-based Single Crystal Alloy Under Shear Loads. Issue 5 (May 2018) - Ben, Li; Shiming, Zhang; Essa, F.A.; Chao, Dong; Jingui, Yu; Qiaoxin, Zhang
Abstract: Crack propagation and microstructural evolution of Ni-based single crystal alloy were investigated under shear load by molecular dynamics simulations. Stress-strain, potential energy and crack growth rates were explored. Moreover, the influences of temperatures and strain rates on crack propagation were revealed. We find that the critical stress value increases with the decreasing temperature or increasing strain rate. As the temperature increases, the crack propagation is accelerated by severe thermal vibrations. Dislocations pile-up and twinning emerge at a higher strain rate, resulting in work hardening.